CASE REPORT : MACULOPAPULAR RASHES IN COVID-19 - Jessica Elizabeth; Yohanes Firmansyah; Sukmawati Tan (Jurnal Medika Hutama, 2021)
Covid-19 itself still has unknown clinical manifestations. Case reports show that the disease spectrum is very large, with several target organs targeted. In general, the recorded symptoms vary from mild to severe, with some cases leading to death. The most frequently reported symptoms to include fever, cough, myalgia or weakness, pneumonia, and extreme dyspnea, although seldom reported symptoms to have headaches, diarrhea, hemoptysis, runny nose, and phlegm cough. One of the most interesting symptoms of COVID-19 is the presence of skin lesions in COVID-19 patients. This case report addresses skin lesions' development in the form of a maculopapular rash on the thirteenth day of infection with COVID-19 and the absence on the fifteenth day of regular care